Acute oral toxicity and safety assessment of Morus alba L. (Moraceae) methanol fruit extract in mice - Sood, Parul; Shri, Richa; Singh, Varinder; F. Ahmad, Sheikh; M. Attia, Sabry (Italian Journal of Food Science, 2024)
Mulberry or Morus alba fruits, belonging to the Moraceae family, are well recognized for their distinct taste and high nutritional content. Nevertheless, studies revealing the toxic effects of fruits are scanty. This study aimed to examine the adverse effects of methanolic fruit extract (MFME) derived from M. alba on mice following OECD 425 guidelines. The female Swiss albino mice were divided into two distinct categories. One group was designated as the control group (administered vehicle), while the other was assigned as the test group (administered 2000 mg/kg MFME orally). Subsequently, behavioral changes were monitored daily, and body weights, relative organ weights, and biochemical and hematological parameters were measured. Additionally, liver, kidney, heart, brain, and ovary assessments were conducted on the 14th day to detect any signs of toxicity. A histopathological investigation was conducted on the anesthetized animals’ vital organs (heart, liver, kidney, brain, and ovary). The study’s findings indicate that the oral administration of MFME did not result in any mortality. Additionally, no significant changes were seen in behavior, food and water intake, biochemical parameters, hematological investigations, and organ weights. Furthermore, the histological analysis revealed no notable pathological alterations in the separated essential organs of mice treated with MFME. The results of this study indicate that the oral administration of MFME is deemed safe up to the maximum test dosage of 2000 mg/kg.